2012
DOI: 10.3354/meps09602
|View full text |Cite
|
Sign up to set email alerts
|

Distribution patterns and nutritional contributions of algal symbionts in the sea anemone Anthopleura xanthogrammica

Abstract: The Pacific intertidal sea anemone Anthopleura xanthogrammica hosts 2 algal symbionts, zoochlorellae Elliptochloris marina and zooxanthellae Symbiodinium muscatinei, either alone or co-occurring. Previous studies have suggested that zoochlorellae and zooxanthellae represent 'cool' and 'warm' symbionts with respect to their field distributions, and that these symbionts may differ in their nutritional contributions to their host. We examined the seasonal distribution, density, and growth of these symbionts in A.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…This tendency for stability over change has raised questions as to whether symbiont shifts are a viable acclimatization strategy for symbiotic cnidarians (Goulet 2006, Thornhill et al 2006). On the other hand, experimental manipulations that simulate environmental change often elicit symbiont shifts (e.g., Rowan et al 1997, Bates 2000, Baker 2001, this study) in symbioses that have been found to be largely stable in nature (Thornhill et al 2006, Levine and Muller-Parker 2012, suggesting that symbiont shifts require environmental perturbations of greater severity or duration than have been commonly observed in nature. Indeed, Baird et al (2007) argue that when forced to acclimatize to enduring environmental changes, such as transplantation experiments or geographical climate gradients, hosts often have the capacity to do so by associating with different algal symbionts.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…This tendency for stability over change has raised questions as to whether symbiont shifts are a viable acclimatization strategy for symbiotic cnidarians (Goulet 2006, Thornhill et al 2006). On the other hand, experimental manipulations that simulate environmental change often elicit symbiont shifts (e.g., Rowan et al 1997, Bates 2000, Baker 2001, this study) in symbioses that have been found to be largely stable in nature (Thornhill et al 2006, Levine and Muller-Parker 2012, suggesting that symbiont shifts require environmental perturbations of greater severity or duration than have been commonly observed in nature. Indeed, Baird et al (2007) argue that when forced to acclimatize to enduring environmental changes, such as transplantation experiments or geographical climate gradients, hosts often have the capacity to do so by associating with different algal symbionts.…”
Section: Discussionmentioning
confidence: 77%
“…Anthopleura symbioses provide an excellent case study of the paradoxically stable yet dynamic nature of cnidarian symbioses: typically characterized by a single dominant symbiont, they are temporally stable over short (annual) time scales (Dimond et al. , Levine and Muller‐Parker ), yet vary geographically (Secord and Augustine ), can be forced to shift experimentally (Saunders and Muller‐Parker , Bates , this study), and are forecasted to shift naturally over longer time scales (Verde and McCloskey , Dimond et al. , Levine and Muller‐Parker ).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations